Analisis Komparatif Kinerja Keuangan Berbasis Rasio Keuangan Pada PT Gudang Garam Tbk dan PT HM Sampoerna Tbk Periode 2015 - 2024 - Saputra, Satrya Yudha; Puji Muniarty (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research analyzes the comparative financial performance of PT Gudang Garam Tbk and PT HM Sampoerna Tbk for 2015-2024 through eight key ratios (current ratio, quick ratio, debt to asset ratio, debt to equity ratio, inventory turnover, total asset turnover, return on asset, return on equity) using quantitative approach with secondary annual financial statement data tested via independent samples T-test for normal data and Mann-Whitney U test for non-normal data at α=0.05. Results indicate five of eight ratios show significant differences (p<0.05) with Sampoerna outperforming on quick ratio (t=-5.679; p=0.000), inventory turnover (t=-12.216; p=0.000), total asset turnover (t=-11.569; p=0.000), return on asset (U=4.000; p=0.001), and return on equity (t=-6.227; p=0.000), while current ratio (U=39.000; p=0.405), debt to asset ratio (t=0.023; p=0.982), and debt to equity ratio (t=-0.407; p=0.689) exhibit no significant differences, reflecting similar conservative capital structures in tobacco industry. The study concludes Sampoerna's superiority derives from superior short-term liquidity, operational efficiency, and asset-equity profitability, recommending Gudang Garam optimize supply chain, Sampoerna innovate low-tar products, and OJK-Ministry of Finance enhance industry efficiency oversight.